A rare beta chain variant hemoglobin Deer Lodge; a chance discovery in an Indian family while testing HbA1c by high-performance liquid chromatography - Dhanani, Hiren J.; Shashtri, Gaurav D.; Tandel, Bharat D.; Modi, Hardik; Kothia, Jaysukh D.; Sukhadiya, Mittal C.; Patel, Asmita; Dhanani, Srushti C.; Dhanani, Nandini H. (International Journal of Research in Medical Sciences, 2025)
This case report documents the first reported instance of hemoglobin (Hb) Deer Lodge in an Indian family, discovered during routine HbA1c testing using high-performance liquid chromatography (HPLC). A 34-year-old clinically asymptomatic male (proband) showed an unexpected peak on HPLC, indicative of a Hb variant. Subsequent family screening revealed the same variant in the proband's mother. Multiple analytical platforms (HPLC and capillary electrophoresis) identified a Hb variant with migration patterns inconsistent with common variants. Genetic sequencing confirmed the HBB:c.8A>G mutation in the β-globin gene, corresponding to Hb Deer Lodge, a rare variant previously reported in non-Indian populations. Additional single nucleotide variants (SNVs), including HBB:c.9T>C, were identified in the family, with some showing high prevalence in the eastern Indian population. Functional analysis suggests that Hb Deer Lodge slightly alters oxygen affinity but remains clinically silent. This report emphasizes the importance of comprehensive analysis for Hb variants detected during routine screening, especially in regions with high genetic diversity. Furthermore, it highlights the potential for rare variants to complicate HbA1c measurements, necessitating confirmatory testing and cautious interpretation in clinical practice.